2016
DOI: 10.1177/0961203316629001
|View full text |Cite
|
Sign up to set email alerts
|

Eppur Si Muove: vitamin D is essential in preventing and modulating SLE

Abstract: Systemic lupus erythematosus (abbreviated SLE or lupus) is a systemic autoimmune disease, with genetic, immunologic, hormonal, and environmental factors.(1)One of the environmental factors that has been studied over the years is vitamin D, which is created in the human body in response to exposure to sunlight and ultraviolet (UV) radiation.This review aims at examining findings from recent years, specifically 2013-2014, regarding the relationship between vitamin D deficiency and SLE flares, severity, and clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 88 publications
1
14
0
1
Order By: Relevance
“…13,[40][41][42] However, interventional studies did not reach definite conclusions regarding the clinical efficacy of vitamin D treatment to treat SLE. 43 Our results are in agreement with another study, which showed that the levels of 25(OH)D were negatively associated with IFN-γ levels. 44 It was demonstrated that 25(OH)D suppresses adaptive immunity, which leads to the inhibition of proliferation and differentiation of CD4 + Th0 cells into Th1 and Th17 cells.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…13,[40][41][42] However, interventional studies did not reach definite conclusions regarding the clinical efficacy of vitamin D treatment to treat SLE. 43 Our results are in agreement with another study, which showed that the levels of 25(OH)D were negatively associated with IFN-γ levels. 44 It was demonstrated that 25(OH)D suppresses adaptive immunity, which leads to the inhibition of proliferation and differentiation of CD4 + Th0 cells into Th1 and Th17 cells.…”
Section: Discussionsupporting
confidence: 93%
“…Although SLE patients are commonly photosensitive and, therefore, may have a greater 25(OH)D deficiency than the general population, 39 in the present study most of the patients have been treated with vitamin D (data not shown), because clinically, it was found that vitamin D deficiency may affect disease activity 13 , 40 , 41 , 42 . However, interventional studies did not reach definite conclusions regarding the clinical efficacy of vitamin D treatment to treat SLE 43 . Our results are in agreement with another study, which showed that the levels of 25(OH)D were negatively associated with IFN‐γ levels 44 .…”
Section: Discussionmentioning
confidence: 53%
“…1 2 In rheumatic diseases in particular, 1,25[OH] 2 D regulates both innate and adaptive immunity, potentiating the innate response, [53][54][55][56] which has been shown to precede the development of autoimmunity in SLE, 57 but reducing adaptive immunity, 53-56 including reduced T cell activation 58 and working in conjunction with glucocorticoids on the inhibition of lymphocyte proliferation. 56 Vitamin D deficiency seems to play a role in increasing B cell activation 14 59 and therefore autoantibody production, and long-term supplementation with vitamin D increased the number of T-regulator cells in individuals with SLE.…”
Section: [Oh]mentioning
confidence: 99%
“…Systemic lupus erythematosus (SLE) is one of the most challenging rheumatic disorders that is possibly influenced by VitD. Despite some contradictory findings, several studies have reported significantly lower serum VitD levels in SLE patients [43][44][45]. Recent data indicated that these lower levels were also associated with an increased risk for moderate to severe SLE manifestations in patients [46].…”
Section: Vitamin D Status In Inflammatory Rheumatic Disordersmentioning
confidence: 99%